Dual-substrate SERS strategy combined with 3D AgNPs substrate for minimally invasive screening and staging of liver cancer - Cong Li; Fuqiang Wang; Lin Xu; Junzheng Wu; Xianqiong Gong; Wei Qiao; Tinghui Lin; Hongyi Zhang; Juqiang Lin (Analytica Chimica Acta, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Irregular-wave transformation over an open-top artificial reef with low-opening-ratio baffles under variable relative submergence - Hongyi Li; Cuiping Kuang; Jiadong Fan; Jilong Chen; Xin Cong; Lin Li (Ocean Engineering, 2026)

Transient receptor potential vanilloid channels in inflammatory bowel diseases: linking inflammation, angiogenesis, and oxidative stress - Peihong Li; Yikun Zhang; Siqing Guo; Hongyi Hu; TingJun Cheng; Kexin Zeng; Tingting Zhang; Linda Zhong; Jiang Lin; Boyun Sun (Inflammopharmacology, 2026)

Spectral energy redistribution and wave attenuation performance of an ecological trapezoidal submerged breakwater under irregular waves - Cuiping Kuang; Weibo Wang; Hongyi Li; Lin Li; Guihui Zhong; Chao Shen (Ocean Engineering, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

MnO2-functionalized membrane with enhanced demulsification and antifouling performance for stable oil-in-water emulsion separation - Sudong Yang; Zhiying He; Mei Zhu; Junjie Zheng; Yixuan Kuang; Hongyi Li; Xueting Yuan; Qing Xu; Qian Zhang; Peng Zhao; Jianmin Luo; Lin Chen (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal evolution and dissipation mechanisms of tidal current turbine wake under different turbulence intensities - Tian Zou; Yajing Gu; Hongwei Liu; Zhiwei Song; Hongyi Lin; Yuquan Zhang (Ocean Engineering, 2026)

Effect of clay content on the coupled seabed response and local scour around a free-spanning pipeline under combined waves and currents - Hongyi Zhao; Fei Lin; Yaru Gao; Zheng Wang; Mengxiao Li; Xiaoli Liu; Shuang Han; Dong-Sheng Jeng (Coastal Engineering, 2026)

Elucidation of Pt-Co synergistic effects in Pt30-Co50@WNxC1−x/W electrodes via operando DRT for enhanced HER kinetics - Yinquan Zhang; Hui Song; Tianjiao Lou; Wenqing Liu; Chunxia Lin; Jiangwen Xu; Guangshun Ran; Jinxu Song; Yukun Chang; Hongyi Li; Jinshu Wang (Chemical Engineering Journal, 2025)

Polyacrylonitrile (PAN) electrospun nanofibrous membrane for removing indoor gaseous phthalates: A health-driven framework for macro-channel adsorption module design and its implications - Yu Sun; Donghui Mo; Lvyan Lin; Hongyi Wang; Jianping Cao; Zhongming Bu (Journal of Hazardous Materials, 2025)

Co-pyrolysis of vancomycin fermentation residue and waste plastics: synergistic effects on pyrolysis behavior, product characteristics, and bio-oil quality enhancement - Hongyi Huang; Zeyu Kang; Xingzhong Huang; Xibing Zhou; Chengbin Zhang; Zhang Lin; Weizhen Liu (Chemical Engineering Journal, 2025)

Morphological and Transcriptomic Response Mediated by Heat Stress in Pleurotus Pulmonarius - Zhenghui Lu; Binrong Ke; Hongyi Lin; Bin Yuan; Lina Ke; Meiyuan Chen; Yuanping Lu (Current Microbiology, 2025)

Evaluation of MODIS NDVI product in a heterogeneous urban environment using five upscaling methods and Landsat 8 product - Haijun Luan; Zhenhong Lin; Chenshuo Xing; Lanhui Wang; Jian Deng; Shangharsha Thapa; Jiajin Zhang; Weibin Wang; Hongyi Yao; Zheng Duan (Remote Sensing Applications: Society and Environment, 2025)

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Comparative analysis in postharvest storability, quality attributes, antioxidant activity, and disease defense systems in ‘Fuyan’ and ‘Dongbi’ longans during storage - Yueying Sang; Lijuan Lin; Hongyi Wen; Yixiong Lin; Mengshi Lin; Yihui Chen; Hui Wang; Zhongqi Fan; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2025)

Transitional behavior of calcareous sand with different clay contents - Hongyi Zhao; Yaru Gao; Fei Lin; Jinhai Zheng; Dong-Sheng Jeng; Shuang Han; Junwei Liu; Yifei Sun (Frontiers in Marine Science, 2025)
Calcareous sand with fines content was often encountered in offshore and onshore engineering. However, most previous research has primarily focused on the mechanical properties of clean calcareous sand. This study conducted a series of drained and undrained triaxial tests on calcareous sand-clay binary mixtures to investigate the impact of fines content on the strength and deformation characteristics of calcareous sand. The results indicate that specimens with varying fines content exhibit both strain hardening and softening behaviors under different confining pressures. With the addition of fines content from 0% to 10%, the extent of dilatancy decreases, resulting in a smaller peak friction angle compared to clean sand specimens. However, when fines content increases further to 25%, both the maximum dilatancy angle and peak friction angle show an increase. A similar trend is observed for the friction angle at the phase transition state (PTS). In the p ′ − q plane, the critical state line (CSL) remains constant despite changes in fines content, whereas in the e − p ′ 0 . 7 plane, the CSL shifts with variations in fines content. A unified CSL in the e − p ′ 0 . 7 plane can be obtained by applying the concept of equivalent skeleton void ratio. Additionally, the state dependence of the material is analyzed using both the modified state parameter and the state index. It was observed that the friction angles at both the PTS and the peak state (PS) are influenced by the state of the material, with the PTS friction angle showing a stronger correlation with the state index, while the PS friction angle is more closely linked to the state parameter.

Microwave-mediated fibrous blended gels of crab meat and surimi: Fibrous protein production method in the perspective of structural remodeling - Qiang Li; Hongyi Wang; Jianfeng Lu; Mengru Yang; Meilin Zhang; Lin Lin; Chenghui Wang (Innovative Food Science & Emerging Technologies, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.

Salicylic acid treatment improves the storability of fresh longan by regulating the metabolisms of respiration and energy - Huili Zhang; Tingting Shan; Yang Chen; Hongyi Wen; Mengshi Lin; Zhongqi Fan; Hui Wang; Yihui Chen; Hetong Lin; Yifen Lin (Postharvest Biology and Technology, 2025)

Phomopsis longanae Chi infection induces changes in the metabolisms of energy and respiration in relation to longan pulp breakdown - Yi Zheng; Jing Yu; Hongyi Wen; Yazhen Chen; Mengshi Lin; Yuzhao Lin; Yueying Sang; Shucheng Li; Yihui Chen; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2025)

Experimental Study of Submarine Pipeline with Geotextile and Stone Cover Protection Under the Superposition of Waves and Currents - Wenqi Si; Mingqing Wang; Yaru Gao; Ke Sun; Bing Chen; Risheng Wang; Lin Cui; Dong-Sheng Jeng; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
Submarine pipelines are the main transport carriers of marine resources. In order to protect these pipelines, geotextile and stone covering measures are adopted in this paper and the protective effect is studied. A sequence of physical model tests was conducted to carry out the research. The hydrodynamic characteristics and seabed oscillation response of the seabed surrounding the pipeline were analyzed with or without geotextile and stone cover protection, and it was found that they were affected by waves (and currents). The experimental results show the following: (1) comparing the regular wave and current with the regular wave alone, it is found that forward current promotes wave propagation and reverse current inhibits wave propagation; (2) the protective effect of geotextile and stone covering measures on different positions of the pipeline (the front, the bottom, and the back of the pipe) is basically same; (3) in the case of waves with large wave heights and long wave periods superimposed with ocean currents, the protective effect of geotextile and stone coverings on the hydrodynamic and seabed pore pressure around the pipeline is more significant.

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

Effects of atmosphere and stepwise pyrolysis on the pyrolysis behavior, product characteristics, and N/S migration mechanism of vancomycin fermentation residue - Hongyi Huang; Shaoyuan Liu; Zeyu Kang; Yiwen Zhu; Chengbin Zhang; E Xiang; Zhang Lin; Weizhen Liu (Chemical Engineering Journal, 2024)

Experimental Study of the Random Wave-Induced Hydrodynamics and Soil Response in a Porous Seabed Around Double Piles - Mingqing Wang; Wenqi Si; Yaru Gao; Lin Cui; Dong-Sheng Jeng; Ke Sun; Bing Chen; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
The evaluation of the wave-induced pore pressures around the offshore piles has attracted great attentions among coastal engineers, because they have been commonly used as foundations of numerous marine infrastructures. This paper presents comparative studies of the random wave-induced transient seabed response around single and double piles in a sandy seabed through a series of wave flume experiments. The influences of relative spacing ratios, wave incidence angles, and front pile diameters under different random wave parameters on oscillatory pore pressures in the vicinity of double piles are examined. In addition, variations in wave profiles and dynamic wave pressures surrounding single and double piles are quantitatively analyzed. Based on the experimental results, the following conclusions can be drawn: (1) under the influence of random waves, the wave profiles around the double piles exhibit obvious irregularity and nonlinearity; (2) the shielding effect existing in the tandem piles results in lower dynamic wave pressures around the rear pile compared to the front pile; (3) the pore pressures on the front surface of the double piles decrease with increasing soil depth, with a decreasing attenuation rate at each layer; (4) when the relative spacing ratio G/D2=3, the group-pile effect weakens, leading to an increase in the pore pressures around the rear pile, approaching the results of a single pile under conditions of lower significant wave heights or periods; (5) the intense disturbance effect caused by large wave incidence angles exacerbates the pore pressure response around the double piles; (6) when the diameter of the front pile in the tandem piles increases, it enhances the shielding effect, thus suppressing the seabed response around the rear pile. In contrast, it causes an increase in the wave surface around the double piles, exacerbating the pore pressure response in the seabed. The latter effect becomes more pronounced when the significant wave height is larger.

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

CO2 mineralization and utilization by tailings sand in China for potential carbon sinks and spatial project layout - Huaqing Li; Yahui Bian; Mingliang Liu; Jianyi Lin; Min Dai; Hongyi Xie; Huajun Yu; Bin Chen; Meili Xue; Zhiwei Li; Jingjing Yin; Liming Xue (Resources, Conservation and Recycling, 2024)

Influence of microorganisms on flavor substances and functional components of sojae semen praeparatum during fermentation: A study integrating comparative metabolomics and high-throughput sequencing - Bin Wang; Yifan Shi; Hongyi Zhang; Yuan Hu; Hongping Chen; Youping Liu; Fu Wang; Lin Chen (Food Research International, 2024)

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Low-abundance proteins-based label-free SERS approach for high precision detection of liver cancer with different stages - Tong Sun; Yamin Lin; Yun Yu; Siqi Gao; Xingen Gao; Hongyi Zhang; Kecan Lin; Juqiang Lin (Analytica Chimica Acta, 2024)

Wavelet transform and deep learning-based obstructive sleep apnea detection from single-lead ECG signals - Yuxing Lin; Hongyi Zhang; Wanqing Wu; Xingen Gao; Fei Chao; Juqiang Lin (Physical and Engineering Sciences in Medicine, 2024)

Identification and validation of key biomarkers and potential therapeutic targets for primary open-angle glaucoma - Jian Wu; Caixia Lin; Chenlong Yang; Lijie Pan; Hongyi Liu; Sirui Zhu; Shuwen Wei; Xu Jia; Qi Zhang; Ziyu Yu; Xiaofang Zhao; Weihai Liu; et al. (Science China Life Sciences, 2023)

Macroevolution of avian T cell receptor C segments using genomic data - Chunhong Liang; Lin Sun; Ying Zhu; Ayong Zhao; Hongyi Liu; Ke He (Immunogenetics, 2023)

High photocatalytic performance of ferroelectric AgNbO3 in a doping state - Lei Jiang; Xiaohua Huang; Yi Zhou; Shengli Huang; Yiwei Wang; Zijian Wang; Dong Sun; Hongyi Lin; Zaijun Cheng (Journal of Environmental Chemical Engineering, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

Recent advances of seabed liquefaction around the vicinity of marine structures - Jie Lin; Dong-Sheng Jeng; Hongyi Zhao; Yuan Gao; Junwei Liu; Yakun Guo (Ocean Engineering, 2023)

Boston ivy-inspired natural-rich binder with strong adhesion for advanced silicon-based anodes - Xiangyu Lin; Yong Wen; Jie Wang; Hongyi Shang; He Liu; Xu Xu (Chemical Engineering Journal, 2023)

Coordination environment dependent stability of Cu-based MOFs towards selective adsorption desulfurization - Canyang Zhang; Xiangdong Xue; Jiangtao Liu; Jing Lin; Xiaowei Zhang; Jitti Kasemchainan; Hongyi Gao; Ge Wang; Xingtian Shu (Chemical Engineering Journal, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Extraction and characterization of pectic polysaccharides from Choerospondias axillaris peels: Comparison of hot water and ultrasound-assisted extraction methods - Chao Wang; Jing Li; Yi Cao; Jialu Huang; Hongyi Lin; Tiantian Zhao; Lu Liu; Peiyi Shen; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; et al. (Food Chemistry, 2023)

Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides - Chao Wang; Yinxin Fu; Yi Cao; Jialu Huang; Hongyi Lin; Peiyi Shen; David Julian McClements; Lingyu Han; Tiantian Zhao; Xiaoxuan Yan; Qian Li (Food Research International, 2023)

Improving probiotic (Lactobacillus casei) viability by encapsulation in alginate-based microgels: Impact of polymeric and colloidal fillers - Qian Li; Hongyi Lin; Jing Li; Lu Liu; Jialu Huang; Yi Cao; Tiantian Zhao; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; Peiyi Shen; et al. (Food Hydrocolloids, 2023)

Dynamic analysis of residential and enterprise water supply and leakage efficiencies - Ying Li; Yung-ho Chiu; Yushan Li; Hongyi Cen; Tai-Yu Lin (Environmental Science and Pollution Research, 2021)

Efficiency assessment of coal energy and non-coal energy under bound dynamic DDF DEA - Ying Li; Tai-Yu Lin; Yung-ho Chiu; Hongyi Cen; Yi-Nuo Lin (Environmental Science and Pollution Research, 2021)

Comparative transcriptome analysis of Apis mellifera antennae of workers performing different tasks - Hongyi Nie; Shupeng Xu; Cuiqin Xie; Haiyang Geng; Yazhou Zhao; Jianghong Li; Wei-fone Huang; Yan Lin; Zhiguo Li; Songkun Su (Molecular Genetics and Genomics, 2018)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)